2017
DOI: 10.1016/j.curtheres.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Repurposed Therapeutic Agents Targeting the Ebola Virus: A Systematic Review

Abstract: BackgroundThe Ebola virus has been responsible for numerous outbreaks since the 1970s, with the most recent outbreak taking place between 2014 and 2016 and causing an international public health emergency. Ebola virus disease (EVD) has a high mortality rate and no approved targeted treatment exists to date. A number of established drugs are being considered as potential therapeutic agents for the treatment of EVD.ObjectiveWe aimed to identify potential drug repositioning candidates and to assess the scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 78 publications
(269 reference statements)
0
44
0
Order By: Relevance
“…Not only does the research focus on the development of a novel drug, but the research is also conducted to identify potential repurposed therapeutic agents for the treatment of Ebola [34,35]. Toremifene and clomiphene, the selective estrogen reuptake modulators, are currently known as the drug to treat breast cancer and infertility, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Not only does the research focus on the development of a novel drug, but the research is also conducted to identify potential repurposed therapeutic agents for the treatment of Ebola [34,35]. Toremifene and clomiphene, the selective estrogen reuptake modulators, are currently known as the drug to treat breast cancer and infertility, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This is worsened by the high level of biocontainment (BSL-4) necessary for the manipulation of this virus that considerably hampers the development of antiviral drugs and vaccines. In this context, DR studies were prompted by the last outbreak (extensively reviewed in [30][31][32]). EBOV provides a unique example of a DR approach applied directly in clinical trials, as during the last outbreak several drugs were evaluated in infected patients (under both clinical trials and compassionate use) to test their ability to protect from lethal EBOV infection.…”
Section: Drug Repurposing For Rna Virus Infectionsmentioning
confidence: 99%
“…These included the viral RNA polymerase inhibitors favipiravir (approved in Japan for the treatment of influenza A virus) [31,33], GS-5734 (an adenosine analog active against highly pathogenic coronaviruses) [34,35], and amodiaquine (an antimalarial drug widely used in Africa). Treatment of EBOV-infected patients with these drugs has been associated with a decrease in fatality rate compared to control patients [30]; however, their efficacy remains to be confirmed in randomized clinical studies. Preclinical DR studies were also performed with both live viruses and pseudoviruses and led to the identification of a series of approved drugs able to confer protection from lethal EBOV infection in animal models.…”
Section: Drug Repurposing For Rna Virus Infectionsmentioning
confidence: 99%
“…The study of favipiravir against Ebola virus has shown good results both in vitro and in vivo. 15 The ability of Chloroquine to inhibit the Ebola virus has shown promising outcomes in different in vitro studies with various cell lines. 16 Toremiphene and clomiphene are widely available selective estrogen reuptake modulators approved for the treatment of breast cancer and infertility, respectively.…”
Section: Repurposing In Ebola Virus Infectionmentioning
confidence: 99%